Metabolic characterization of selected probiotic consortia during gluten and wheat bread simulated digestion - Mirco Vacca; Giuseppe Celano; Olga Nikoloudaki; Bodo Speckmann; Francesco Maria Calabrese; Marco Gobbetti; Maria de Angelis (Food Science and Human Wellness)
While exerting their metabolic activities in the gastrointestinal milieu, probiotics impact the host well-being by boosting immunity, treating metabolic disorders, and modulating microbiota and metabolome. Due to the high incidence of gluten-based disorders, the present work aims to deeply explore the metabolism of two selected microbial consortia (MCs) during gluten digestion under simulated gastrointestinal conditions. Featured by high protease and peptidase activity, both MCs accounted for different lactic acid bacteria and Bacillus strains that were combined with two commercial protease enzymes. Gluten substrates were used as purified extracts, white and whole wheat breads. Control samples, instead, relied onto the microbial enzyme lack. Twenty-four hours of simulated digestion were sufficient to completely hydrolyze gluten in one of the two MC-containing experimental sets, and the relative 48 h-digested extract did not alter the cytokine expression in duodenal biopsies from celiac disease (CeD) patients. When digested samples were assayed for antioxidant and phytase activities, microbial enzymes demonstrated to significantly improve both 2,2’-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS) and 1,1-diphenyl-2-picrylhydrazyl (DPPH) scavenging activity and to decrease the phytic acid concentration. The inspection of the free amino acid profiles allowed for distinguishing the two MCs, whereas the detection of a heterogeneous panel of volatile organic compounds supported the presence/activity of microbial enzymes without statistically significant differences between MCs. As functional contribution, digested extracts with MCs also proved to reduce the inflammatory cytokine concentrations in cell lines exposed to lipopolysaccharide trigger. Therefore, in line with studies exploring novel adjuvant therapies, the present innovative probiotic consortium featured by high gluten-hydrolyzing metabolism also showed the capability to improve various parameters usually found to be altered in patients affected by gluten-based disorders or CeD.